Magnetic moment of Mn2+ ions that are responsible for the ferromagnetic properties of ZnO:Mn nanocrystals - Kovalenko, O.V.; Vorovsky, V.Yu. (Physics and Chemistry of Solid State, 2023)
The calculation of the magnetic moment of Mn2+ ions in ZnO:Mn (2 at%.) nanocrystals obtained by ultrasonic pyrolysis of aerosol which are responsible for their ferromagnetic properties is given. In order to investigate the influence of structural defects on the value of magnetic moment the samples were heat treated in air. The calculation was performed on the basis of the analysis of magnetization curves and EPR spectra. It was shown that the defective state of ZnO:Mn nanocrystals has a significant effect on the magnetic moment. The values of magnetic moment for the synthesized sample significantly exceed the values of magnetic moment compared to similar nanocrystals obtained by other methods. The assumption is made that this result is due to the presence of an additional component in the magnetization of the defective samples. In addition to the paramagnetism of Mn2+ ions, there may be the paramagnetism of the defective shell of ZnO:Mn nanocrystals. After the elimination of structural defects by heat treatment of samples in air and in a gas mixture with hydrogen, the magnetic moment for Mn2+ ions, which form the ferromagnetic properties of nanocrystals, was determined. The value of this magnetic moment is 0.02µB, where µB is the Bohr mangiton. Such ions, according to the model of bound magnetic polarons, are part of ferromagnetic clusters and take part in the formation of the ferromagnetic properties of the samples. Keywords: magnetic moment, nanocrystals, ultrasonic aerosol pyrolysis, heat treatment, hydrogen.